2001
DOI: 10.1038/sj.onc.1204909
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal regulation of DDB2 gene expression in xeroderma pigmentosum group E strains

Abstract: A damage-speci®c DNA binding protein (DDB) activity is absent from a subset (DDB 7 ) of cells from individuals initially classi®ed as group E of xeroderma pigmentosum (XP), a hereditary, photosensitive disease with a high incidence of skin malignancies. In these cases, mutations have been identi®ed in the DDB2 gene (DDB2 7 ) that codes for the small subunit, p48, of the DDB heterodimer. In four DDB2 7 strains, neither p48 nor DDB activity were observed before or after UVirradiation, despite an unusually strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Therefore, levels of DDB2 protein in the mouse cells were estimated from damaged DNA binding assays (Fig. 3B). [In human diploid fibroblasts, levels of DDB2 protein are limiting for the DDB heterodimer and paralleled damaged DNA binding activity (1,3).] Consistent with the observations in normal human cells (1,18), DDB activity decreased on irradiation and then reappeared after DNA repair was largely completed in the mouse DDB2 ϩ/ϩ cells (Fig.…”
Section: Consequences Of Disruption Of Thesupporting
confidence: 73%
“…Therefore, levels of DDB2 protein in the mouse cells were estimated from damaged DNA binding assays (Fig. 3B). [In human diploid fibroblasts, levels of DDB2 protein are limiting for the DDB heterodimer and paralleled damaged DNA binding activity (1,3).] Consistent with the observations in normal human cells (1,18), DDB activity decreased on irradiation and then reappeared after DNA repair was largely completed in the mouse DDB2 ϩ/ϩ cells (Fig.…”
Section: Consequences Of Disruption Of Thesupporting
confidence: 73%
“…RT-PCR was performed as described previously (27). The following DDB2 primers were used for semiquantitative RT-PCR: S5 (nucleotides ϩ871 to ϩ890) and AS6 (nucleotides ϩ1151 to ϩ1170) and S2 and AS3.…”
Section: Fig 2 Reduced Levels Of P53 and Several Of Its Target Genementioning
confidence: 99%
“…Since nucleotide excision repair (NER) is all but complete 48 h after UV irradiation (13), and since NER reconstitution studies have shown that DDB is not required for NER in vitro (1,35), the direct function, if any, of DDB in DNA repair is unclear. In XP-E cell strains, p48 DDB2 protein and DDB activity are undetectable after UV irradiation (except in strain XP82TO), yet DDB2 mRNA levels are abnormally high both before (2-to 4-fold) and after (11-to 37-fold) UV irradiation (27). However, the regulation of DDB2 induction after UV damage is poorly understood.…”
mentioning
confidence: 99%
See 2 more Smart Citations